Evaluation of oral health in a community of native brazilians of the umutina reservation, Mato Grosso State - Vieira, Evanice Menezes Marçal [UNESP] (2011)
The occurrence of diseases and variations from normality is very common in the maxillofacial complex, and this phenomenon is closely associated to peculiar genetic determinants and influenced by genetic isolation. Studies on the distribution of oral diseases and variations from normality in South American natives are generally directed mainly to the study of dental caries in the children and periodontal diseases in the adults, disregarding a wide range of other oral diseases. The aim of this study was to evaluate the distribution of lesions and anatomical variations from normality in eight ethnic groups living in the Umutina Indian Reservation, State of Mato Grosso, Brazil, through physical and oral examinations besides cytological evaluation and assessment of diet and habits, such as tobacco and alcohol consumption. A total of 291 Indians, of both genders, with ages ranging from 1 to 96 years, were examined, being identified 132 variations from normality, evidencing a high occurrence of ankyloglossia, which was present in 108 cases (37.1%), followed by benign migratory glossitis in 5 cases (1.7%); mandibular torus and candidiasis in 3 cases (1.0%). No malignant lesion was identified in the population.